Inequity under equality: research on the benefits equity of Chinese basic medical insurance - Li Diao; Yiwei Liu (BMC, 2020)
Abstract Background The pursuit of equity is one of the basic principles behind the strengthening of health care reform. China's new rural cooperative medical insurance (NRCMI) and urban residents' basic medical insurance (URBMI) are both "equalized" in terms of fundraising and reimbursement. This paper studies the benefits equity under this "equalized" system. Methods The data analysed in this paper are from the China Family Panel Studies (CFPS) from 2014 to 2016, implemented by the Institute of Social Science Survey at Peking University. A two-part model and a binary choice model are used in the empirical test. Results The empirical test revealed that high-income people benefit more from basic medical insurance than low-income people. Mechanism analysis demonstrated that high-income people have higher medical insurance applicability and can utilize better health care. Since low-income people are unhealthier, inequity in benefits exacerbates health inequity. We also found that the benefits equity of URBMI is better than that of NRCMI. Conclusions The government needs to pay more attention to the issue of medical insurance inequity. We should consider allowing different income groups to pay different premiums according to their medical expenses or applying different reimbursement policies for different income groups.